Peran Guru dalam Pengembangan Sikap Toleransi Beragama pada Anak Usia Dini (THUFULA, 2018)
THE ROLE OF TEACHERS IN DEVELOPING RELIGION TOLERANCE ATTITUDES IN EARLY CHILDHOOD. This study aims to describe the role of teachers based on their competencies and sub- competencies as educators to develop religious tolerance. This research is a descriptive qualitative research conducted at TK Negeri Pembina Karangmalang Sragen. The results of this study revealed that religious tolerance was developed through several parts of development which included: 1) Development of an attitude of respecting the content of prayer, 2) Development of an attitude of respect for prayer and worship, 3) Development of respect for religious symbols, 4) Development of respect for halal-haram concepts, and 5) Development of an attitude of understanding the different names of God. Certain sub-competencies in pedagogical, personality, professional and social competencies are needed to support the role of teachers in developing religious tolerance in early childhood.